Evaluation of in-vitro anti-urolithiatic activity of ethanolic extract of sterculia urens - B, Nirmala Devi; D, Swarnalatha (International Journal of Indigenous Herbs and Drugs, 2022)
All individuals have traditionally considered medicinal plants as a healthy source of life, and its therapeutic characteristics have proven to be quite effective in treating a wide range of illnesses. Another benefit of using medicinal plants is that they are completely natural. Since ancient times, people have utilized traditionally to treat common infectious disorders, and the belief that some plants possessed therapeutic properties was widely recognized even before mankind discovered there were microorganisms. Due to their antibacterial qualities, several plants have been utilised in traditional medicine for a long time. The therapeutic benefit of these plants is specifically found in a few chemical compounds that have a clear physiological effect on the human or animal body. Alkaloids, flavonoids, tannins, and phenolic compounds are among these bioactive ingredients, which are primarily secondary metabolites, that are most significant. Cells of microorganisms are poisoned by these phytochemicals. Individuals with Nephrolithiasis or kidney stone disease, is a condition that accumulate calculi (stones) within the renal pelvis and tubular lumens. Stones are formed when crystals precipitate (separate) from urine. When the urine concentration of compounds that help prevent stone formation (citrate) is low or when that of substances that help create crystals (calcium, oxalate, and uric acid) is high, stones may form. Current research aims for assessment of the invitro anti urolithiatic activity of Sterculia urens by employing the method such as nucleation assay Our study indicates that, sterculia urens can be a great source of antiurolithiatic agents, which are most likely mediated by the suppression of CaOx crystallization.